2021
DOI: 10.1537/ase.201215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring models of human migration to the Japanese archipelago using genome-wide genetic data

Abstract: The origins of people in the Japanese archipelago are of long-standing interest among anthropologists, archeologists, linguists, and historians studying the history of Japan. While the 'dualstructure' model proposed by Hanihara in 1991 has been considered the primary working hypothesis for three decades, recent advances in DNA typing and sequencing technologies provide an unprecedented amount of present-day and ancient human nuclear genome data, which enable us to refine or extend the dual-structure model. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Then, variant information from all samples was joined to make a variant database using the GenomicsDBImport of GATK. We then used the Geno-typeGVCFs of GATK to extract multi-sample variant calls in the Variant Call Format (VCF) (Osada and Kawai, 2021). ( 7) We then conducted the Variant Quality Score Recalibration (VQSR) using VariantRecalibrator and ApplyVQSR, machine-learning algorithms of GATK which incorporate known variant site information.…”
Section: Processing Of Ngs Read Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Then, variant information from all samples was joined to make a variant database using the GenomicsDBImport of GATK. We then used the Geno-typeGVCFs of GATK to extract multi-sample variant calls in the Variant Call Format (VCF) (Osada and Kawai, 2021). ( 7) We then conducted the Variant Quality Score Recalibration (VQSR) using VariantRecalibrator and ApplyVQSR, machine-learning algorithms of GATK which incorporate known variant site information.…”
Section: Processing Of Ngs Read Datamentioning
confidence: 99%
“…Building on this previous research, we focus on the Japanese population as a case study of OR gene family variation. The Japanese population is a hybrid between the Yayoi people, farmers who migrated from the East Eurasian Continent ~3000 years ago, and the Jomon people, indigenous huntergatherers who were likely to be the descendants of late-Paleolithic people in the Japanese archipelago (Hanihara, 1991;Adachi et al, 2021;Jinam et al, 2021;Koganebuchi and Oota, 2021;Osada and Kawai, 2021). Ancient DNA analyses inferred that the Jomon people diverged from the current East Asians earlier than 26000 years ago (McColl et al, 2018;Gakuhari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was also revealed that the Jomon people were genetically closely related to the Ainu/Ryukyuan, and that 10–20% of genomic components found in mainland Japanese are derived from the Jomon people 8,10 . Recent studies found that, in addition to the “East Asian” population which is closely related to modern Han Chinese, the “Northeast Asian” population also contributed to the ancestry of modern Japanese 12,13 . Cooke et al 2021 showed the deep divergence of the Jomon people from continental populations including the “East Asians” and “Northeast Asians”, so it can be concluded that the modern mainland Japanese are a population with genomic components derived from a basal East Asian lineage (i.e., the Jomon people) and from continental East Asians.…”
Section: Introductionmentioning
confidence: 99%
“…Two review articles were contributed by Group B03 (Osada and Kawai) and by Group A04 (Koganebuchi and Oota). Osada and Kawai (2021) reviewed usage of genomewide SNP data for estimating human migrations to Yaponesia. Koganebuchi and Oota (2021) reviewed human paleogenomic studies in East Asia including Yaponesia.…”
mentioning
confidence: 99%
“…Koganebuchi and Oota (2021) reviewed human paleogenomic studies in East Asia including Yaponesia. Although it is a review article, Osada and Kawai (2021) found a weak but significant genetic tie of Jomon people to ancient North Siberians through meta-analysis of publicly available datasets.…”
mentioning
confidence: 99%